Paleomagnetic and rock magnetic study with emphasis on the Precambrian intrusions and impact structures in Fennoscandia and South Africa - Salminen, Johanna (Helsingin yliopisto, 2010)
The importance of supercontinents in our understanding of the geological evolution of the planet Earth has been recently emphasized. The role of paleomagnetism in reconstructing lithospheric blocks in their ancient paleopositions is vital. Paleomagnetism is the only quantitative tool for providing ancient latitudes and azimuthal orientations of continents. It also yields information of content of the geomagnetic field in the past. In order to obtain a continuous record on the positions of continents, dated intrusive rocks are required in temporal progression. This is not always possible due to pulse-like occurrences of dykes. In this work we demonstrate that studies of meteorite impact-related rocks may fill some gaps in the paleomagnetic record. This dissertation is based on paleomagnetic and rock magnetic data obtained from samples of the Jänisjärvi impact structure (Russian Karelia, most recent 40Ar-39Ar age of 682 Ma), the Salla diabase dyke (North Finland, U-Pb 1122 Ma), the Valaam monzodioritic sill (Russian Karelia, U-Pb 1458 Ma), and the Vredefort impact structure (South Africa, 2023 Ma). The paleomagnetic study of Jänisjärvi samples was made in order to obtain a pole for Baltica, which lacks paleomagnetic data from 750 to ca. 600 Ma. The position of Baltica at ca. 700 Ma is relevant in order to verify whether the supercontinent Rodinia was already fragmented. The paleomagnetic study of the Salla dyke was conducted to examine the position of Baltica at the onset of supercontinent Rodinia's formation. The virtual geomagnetic pole (VGP) from Salla dyke provides hints that the Mesoproterozoic Baltica - Laurentia unity in the Hudsonland (Columbia, Nuna) supercontinent assembly may have lasted until 1.12 Ga. Moreover, the new VGP of Salla dyke provides new constraint on the timing of the rotation of Baltica relative to Laurentia (e.g. Gower et al., 1990). A paleomagnetic study of the Valaam sill was carried out in order to shed light into the question of existence of Baltica-Laurentia unity in the ...